Clinical challenges in diagnosing idiopathic mesenteric phlebosclerotic colitis: two case reports and an up-to-date literature review - Shang, MingYan; Yin, Liang; Li, Zhangzhu; Gan, Jie; Wang, Jing (Frontiers in Gastroenterology, 2025)
Idiopathic mesenteric phlebosclerotic colitis (IMP) is a rare ischemic colitis primarily affecting the right colon, characterized by mesenteric venous sclerosis and calcification. Its etiology remains unclear, but prolonged use of traditional Chinese herbal medicines, particularly those containing gardeniae fructus, has been suggested as one of several contributing factors, alongside metabolic disorders and potential genetic predispositions. This case report highlights two cases of IMP linked to herbal medicine use, providing insights into its pathogenesis, diagnosis, and management. Both patients were diagnosed with IMP based on CT imaging and histopathology. Management involved discontinuation of herbal treatments, dietary modifications, and controlling metabolic conditions. Both patients had stable outcomes with no disease progression upon follow-up. This case report underscores the importance of considering IMP in patients with unexplained ischemic colitis, particularly those with a history of long-term herbal medicine use. Early intervention, including discontinuation of herbal remedies and management of metabolic factors, is crucial for preventing disease progression. Further research is needed to better understand the pathophysiology of IMP and its relationship with herbal medicine.